Fundamental of Entrepreneurship ENT300 : Spaphile Company / Ali Patrick ... [et al.] - Patrick, Ali; Hashim, Khairunnisha; Ismail, Nur Anisah; Sabriee, Nur Liyana; Yong, Nurul Hayati (2014)
After doing extensive research on the business opportunity available in Kota Samarahan area, our group decided to specify our business. Our group has come up with the business plan of partnership, known as SPAPHILE Company. The business has been decided on the form of five partnerships. Each partner has contributes certain amount of capital as agreed in our agreement. We will open our spa at Uni Garden, Kota Samarahan, Sarawak and hopefully will open by 1st January 2015. The members include general manager, marketing manager, operational manager, administrative manager and financial manager. All partners are encourage and entitled to participate in all business management. We had appointed Khairunisha binti Hashim as General Manager, Ali bin Patrick as our Marketing Manager, Nurul Hayati binti Yong as our Operational Manager, Nur Anisah binti Ismail as Administrative manager and Nur liyana binti Sabriee as our Financial Manager.